Exploring the present and target academic English language needs of Iranian undergraduate students: a case at the Tabriz University of Medical Sciences - Simin Sattarpour; Assef Khalili (Research and Development in Medical Education, 2019)
Background: The content for courses for English for specific purposes (ESP) has been largely determined on the basis of the intuitive judgments and personal preferences of syllabus designers and teachers rather than a standard needs analysis. The present study was an attempt at assessing the current English language abilities of undergraduate students majoring in the medical sciences and identifying their target needs for academic success through quantitative and qualitative methods. Methods: The participants included 197 undergraduate students, 12 Teaching English as a Foreign Language (TEFL) teachers, and 15 content teachers from the Tabriz University of Medical Sciences, Iran. Data were collected through a target needs analysis, self-assessment questionnaires, and semi-structured interviews. Results: Pronunciation, technical and general vocabulary knowledge, and use of bilingual dictionaries were regarded as ‘important’ and ‘very important’ target needs by the participants, though some significant differences in perceptions were found between content teachers and students. Writing skill, listening comprehension, and speaking were perceived as the weakest points in the students’ current level of ability. There was also a significant difference between the perception of TEFL teachers and students in assessing the students’ linguistic abilities. Furthermore, both students and TEFL teachers voiced their dissatisfaction with certain areas of ESP courses, such as an inadequate number of credits and heterogeneity of classes. Conclusion: To improve the outcome of ESP courses, they should be designed on the basis of a realistic appreciation of all stakeholders’ perceptions in the field, and they should be taught through the cooperation of both TEFL teachers and content teachers working together.